2010
DOI: 10.1111/j.1365-2958.2010.07100.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex interplay between the LysR‐type regulator AtzR and its binding site mediates atzDEF activation in response to two distinct signals

Abstract: SummaryAtzR is a LysR-type regulator responsible for activation of the cyanuric acid utilization operon atzDEF. AtzR binds the PatzDEF promoter region at a strong recognition element, designated the repressor binding site, and a weaker binding determinant, the activator binding site (ABS). AtzR activates transcription in response to two dissimilar signals, nitrogen limitation and cyanuric acid. In the present work we analyse the structure and function of the cis-acting elements involved in AtzR activation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 36 publications
0
38
1
2
Order By: Relevance
“…In addition, hypersensitive positions were noted at Ϫ139, Ϫ136, Ϫ129, Ϫ100, Ϫ99, Ϫ90, and Ϫ85 (bottom strand) and Ϫ130, Ϫ96, Ϫ95, Ϫ87, Ϫ86, and Ϫ85 (top strand). Continuous protection of the RBS and the presence of strongly hypersensitive positions downstream from the RBS were reminiscent of the AtzR interaction with the PatzDEF promoter region and suggested that AtzR bends DNA upon binding (40,42). However, unlike the PatzDEF promoter region, additional protected positions extending toward the PatzT promoter were not observed, suggesting that the interaction of AtzR with DNA outside the strong RBS element is likely very weak or absent.…”
Section: Transcriptional Organization Of the Atzrstuvw Operonmentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, hypersensitive positions were noted at Ϫ139, Ϫ136, Ϫ129, Ϫ100, Ϫ99, Ϫ90, and Ϫ85 (bottom strand) and Ϫ130, Ϫ96, Ϫ95, Ϫ87, Ϫ86, and Ϫ85 (top strand). Continuous protection of the RBS and the presence of strongly hypersensitive positions downstream from the RBS were reminiscent of the AtzR interaction with the PatzDEF promoter region and suggested that AtzR bends DNA upon binding (40,42). However, unlike the PatzDEF promoter region, additional protected positions extending toward the PatzT promoter were not observed, suggesting that the interaction of AtzR with DNA outside the strong RBS element is likely very weak or absent.…”
Section: Transcriptional Organization Of the Atzrstuvw Operonmentioning
confidence: 90%
“…Gel mobility shift assays with AtzR were performed essentially as described previously (42). Probes containing the wild-type and the mutant versions of the AtzR binding site (AtzR-L, AtzR-R, and AtzR-LR) were obtained by PCR using the corresponding lacZ fusion plasmids pMPO805, pMPO815, pMOPO816, and pMPO821 as templates and oligonucleotides Del-RBS and R-SalI as primers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several LTTRs are known to activate gene expression as higher oligomeric complexes, which form on recognition of their cognate signals (2,53,55,57). Studies on the classical LysR regulator OxyR, which forms oligomeric complexes when oxidized, suggest that a subset of LTTRs are activated via a redox-sensing mechanism (2,69,70,72).…”
mentioning
confidence: 99%